Structure and resistance to mechanical stress and enzymatic cleaning of Pseudomonas fluorescens biofilms formed in fresh-cut ready to eat washing tanks. (December 2019) - Cunault, Charles; Faille, Christine; Calabozo-Delgado, Almudena; Benezech, Thierry
Abstract: Surface contamination by Pseudomonas fluorescens biofilms was studied using pilot scale washing tanks with standard design features encountered in the fresh-cut vegetable processing industry. Consequences on the biofilms' resistance to the shear stress and to enzymatic cleaning were analysed. It was found that biofilm structures depended on the location in the tanks, which could range from discontinuous monolayer to large thick clusters, as observed for the wetting front areas corresponding to intermittently immersed areas. Biofilms grown in zones subjected to shear and at the wetting front were significantly more resistant to mechanical stress. Therefore, poor design features such as horizontal surfaces, right angles, welds and corners at the vat bottom appeared critical in terms of hygiene, being more resistant to enzymatic cleaning. Biofilms developed at the wetting front, in a priori hygienic areas, also appear resistant to enzymatic cleaning, constituting additional critical areas. Highlights: Biofilm formation and structure are strongly related to the equipment design. Resistant biofilms are observed on surfaces at the wetting front. Biofilms grown under mechanical stress are highly resistant to shear stress. Biofilms grown on horizontal surfaces are difficult to clean by enzymes.